Alginate-Encapsulation for the Improved Hypothermic Preservation of Human Adipose-Derived Stem Cells. (29th January 2016) - Swioklo, Stephen; Constantinescu, Andrei; Connon, Che J.
Abstract: : Despite considerable progress within the cell therapy industry, unmet bioprocessing and logistical challenges associated with the storage and distribution of cells between sites of manufacture and the clinic exist. We examined whether hypothermic (4°C–23°C) preservation of human adipose-derived stem cells could be improved through their encapsulation in 1.2% calcium alginate. Alginate encapsulation improved the recovery of viable cells after 72 hours of storage. Viable cell recovery was highly temperature-dependent, with an optimum temperature of 15°C. At this temperature, alginate encapsulation preserved the ability for recovered cells to attach to tissue culture plastic on rewarming, further increasing its effect on total cell recovery. On attachment, the cells were phenotypically normal, displayed normal growth kinetics, and maintained their capacity for trilineage differentiation. The number of cells encapsulated (up to 2 × 10 6 cells per milliliter) did not affect viable cell recovery nor did storage of encapsulated cells in a xeno-free, serum-free, current Good Manufacturing Practice-grade medium. We present a simple, low-cost system capable of enhancing the preservation of human adipose-derived stem cells stored at hypothermic temperatures, while maintaining their normal function. The storage of cells in this manner has great potential for extending the time windows for quality assurance and efficacy testing, distribution between the sites of manufacture and the clinic, and reducing the wastage associated with the limited shelf life of cells stored in their liquid state. Significance: Despite considerable advancement in the clinical application of cell-based therapies, major logistical challenges exist throughout the cell therapy supply chain associated with the storage and distribution of cells between the sites of manufacture and the clinic. A simple, low-cost system capable of preserving the viability and functionality of human adipose-derived stem cells (a cell with substantial clinical interest) at hypothermic temperatures (0°C–32°C) is presented. Such a system has considerable potential for extending the shelf life of cell therapy products at multiple stages throughout the cell therapy supply chain. Abstract : A simple, low-cost system to enhance the preservation of human adipose-derived stem cells stored at hypothermic temperatures, while maintaining their normal function, is presented. This system has great potential for extending the time windows for quality assurance and efficacy testing, distribution between the sites of manufacture and the clinic, and reducing the wastage associated with the limited shelf life of cells stored in their liquid state.